Addressing collective action problems in Melanesia: the Northern Islands Market Vendors' Association in Vanuatu. Issue 8 (16th November 2020) - Barbara, Julien; Baker, Kerryn
ABSTRACT: This article presents case study findings on the Vanuatu-based Northern Islands Market Vendors' Association (NIMVA) as a vehicle for women-led collective action. While NIMVA's existence and organisational strength challenges existing political norms, strong gender norms restricting the role of women in society and politics continue to marginalise its capacity to participate politically and pursue transformative change. Using a "permitted empowerment" frame, the article assesses NIMVA's emergence as a vehicle for women market vendors to undertake collective action to improve livelihoods, and the implications for those seeking to support more inclusive forms of local-level development.